IDENTIFICATION OF SITUATIONAL CONTEXT AS THE MAIN PURPOSE OF TEACHING PAREMIOLOGICAL UNITS TO FOREIGN STUDENTS (EXAMPLES OF RUSIIAN AND TURKISH LANGUAGES) - I. B. Ignatova; Р. Umut (Вестник Кемеровского государственного университета, 2014)
The purpose of this article is to present some methodological recommendations for teaching foreign students to recognize the paremiological context and select the most precise paremiological unit for description of the situation. Besides, the article concerns such aspects as variability and incompleteness of proverbs and sayings as a typical feature of Russian and Turkish languages. The examples of exercises forming students’ language competence are given.